Freedom of Association, Social Cohesion and Welfare - Hernández, Penélope (My University, 2017)
How does freedom of association shape social cohesion, individual behavior and welfare, in heterogeneous populations? To answer this question, we develop a theoretical model and conduct experiments with human subjects. We study a network formation and action choice game in which individuals benefit from selecting the same action as their neighbours. However, one group of individuals prefers to coordinate on one action, while the rest prefers to coordinate on the other action.
Keywords: Libertad de asociación